Analysis and Assessment of Security in Cyber-Physical Systems - Abbasova, P.A. (Herald of Azerbaijan Engineering Academy, 2025)
With the digitalization of the world, cyber attacks have entered our lives, initially pos-sessing a simple and easily understandable structure. However, today they have become increas-ingly complex and difficult to investigate. To address this problem, the collection of intelligence data related to attacks before they occur, and their detection after they happen, have become two essential components of modern cybersecurity. In particular, the successful integration of large-scale network infrastructures into the field of cybersecurity in recent times has made it necessary to utilize these technologies both in cyber threat intelligence and attack detection systems. This study explores cyber threat intelligence, attack detection systems, and large-scale network tech-nologies, reviews the work focused on cyber threat intelligence and attack detection systems that utilize large network technologies, and provides various evaluations.